2011
DOI: 10.2166/wh.2011.051
|View full text |Cite
|
Sign up to set email alerts
|

Drinking water consumption patterns in Canadian communities (2001–2007)

Abstract: A pooled analysis of seven cross-sectional studies from Newfoundland and Labrador, Waterloo and Hamilton Regions, Ontario and Vancouver, East Kootenay and Northern Interior Regions, British Columbia (2001 to 2007) was performed to investigate the drinking water consumption patterns of Canadians and to identify factors associated with the volume of tap water consumed. The mean volume of tap water consumed was 1.2 L/day, with a large range (0.03 to 9.0 L/day). In-home water treatment and interactions between age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…It would have been ideal to be able to model the risk factors for choosing primarily tap water for comparison to choosing primarily bottled water, rather than comparison to drinking their tap water on a daily basis. Previous studies have suggested that water consumption decreases with age [8,9,15], which could make daily tap water consumption an especially poor proxy for choosing primarily tap water in older age groups. Overall, the purposive nature of our regional sampling and a relatively low response rate, especially among younger age groups (Table 2), might limit the generalizability of our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would have been ideal to be able to model the risk factors for choosing primarily tap water for comparison to choosing primarily bottled water, rather than comparison to drinking their tap water on a daily basis. Previous studies have suggested that water consumption decreases with age [8,9,15], which could make daily tap water consumption an especially poor proxy for choosing primarily tap water in older age groups. Overall, the purposive nature of our regional sampling and a relatively low response rate, especially among younger age groups (Table 2), might limit the generalizability of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Treating the tap water was evaluated as a dichotomous outcome based on the response to a question asking if the respondent had any equipment in their home to make the tap water better or safer to drink. Because the use of in-home treatment devices has been examined as a predictor of water consumption patterns in other studies [9,12,15], the use of water treatment in the home was also assessed as a risk factor in the models for bottled and tap water choices. …”
Section: Methodsmentioning
confidence: 99%
“…(64,65) The frequency of consuming water (amount consumed per day) was estimated from a literature review. (66) The prevalence and concentration estimates were based on a literature review and FoodNet Canada surveillance data. (40,41,(67)(68)(69)(70)(71) The exposure to Campylobacter cells from recreational water was estimated using a variety of values from the literature, FoodNet Canada data, and Foodbook.…”
Section: Data Sourcesmentioning
confidence: 99%
“…In addition, populations with lower socioeconomic status may perceive tap water as less safe (3,4,6,811). Previous studies have relied on convenience samples (36,911,13) and qualitative data (3,4,9,10,12), have been descriptive (1,3,6,913,16,17), have focused on water intake only (1,16,18), have included only children (2,6,18,19), or did not include race/ethnicity (8,1012,15). Our objective was to examine differences in tap water consumption and perceptions of bottled versus tap water safety for Hispanics and non-Hispanic whites, as well as associations with other demographic characteristics, by using a random and representative sample of adults.…”
Section: Objectivementioning
confidence: 99%